Iнформацiйна технологiя вивчення кисневого режиму м'язової клiтини - Лябах, К.Г.; Духновська, К.К. (Cybernetics and computer engineering, 2020)
Мета роботи — створення зручної для користувача технології аналізу кисневого режиму клітини з гетерогенністю потужності мітохондрій всередині міоциту людини. Результати. За допомогою розробленої технології моделюється транспорт кисню в системі «кров — клітина — мітохондрії», задаються параметри кровотоку і киснево-транспортних властивостей крові, навантаження, геометрія капілярів досліджуваної клітини, а також нерівномірність розподілу мітохондрій, як споживачів кисню. Результати розрахунків різних режимів характеризують їх в цілому і в різних точках клітини, вони надаються користувачеві у вигляді таблиць, графіків і опису полів в матричній формі, їх легко зіставляти між собою на одному екрані. The purpose of the paper is to create a user-friendly technology for the analysis of the oxygen regime of the cell with the heterogeneity of mitochondrial oxidative power within the human myocyte in the blood-cell-mitochondria system. Blood flow, its oxygen-transport properties, load, capillary geometry, as well as uneven distribution of mitochondria as oxygen consumers are the basic parameter for calculations Results. The technology is designed to use a standard set of indicators of O2 transport and utilization to study the oxygen supply of working human skeletal muscle. It gives a possibility to study mitochondria under hypoxia that regulate oxygen cell supply by different ways. The proposed technology allows studying the effect of mitochondrial reorganization that occurs under some conditions, on the adaptation processes of the cell working under another one. The technology revealed the importance of the connection between the intercapillary distance and the heterogeneity of mitochondria as a factor influences on tissue oxygen regime.